Perbandingan Kebocoran Tepi Resin Komposit NanofillDengan Polimerisasi Sinar Light Cure DenganTeknik Ramped Dan Pulse Delay - Ningrum, Puspita Wahyu; , drg. Noor Hafida Widyastuti, Sp.KG; , drg. Budi Dewantari (2017)
Nanofill composite resin has mechanical strength, a good aesthetic and the advantages of nanofill composite resin was a good result of polishing. The weakness of nanofill composite resin was shrinkage which could cause microleakage. Microleakage can be prevented with low radiation levels with soft start radiation. The kind of soft start radiation such as stepped, ramped and pulse delay. The aim of the study was to determined the differences of ramped and pulse delay radiation to nanofill composite resin's microleakage. The study used 32 premolar teeth which been prepared into class V and divided into two groups. Group I teeth were restored with polymerization nanofill composite resin by using ramped radiation technique and in group II by using pulse delay radiation technique during 40 seconds. Specimens were immersed in methylene blue 2% for 24 hours then centrifuged. Teeth were sectioned and evaluated used a stereomicroscope at 12x magnification. Statical analysis were performed with Shapiro-wilk test (p>0,05), levene's test (p>0,05) and Independent t-test (p<0,05). The result showed there were significant differences between ramped and pulse delay radiation to microleakage which the polymerization of microleakage with pulse delay radiation was better than ramped radiation.